2001
DOI: 10.1021/la0010018
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Interaction between Cellulose Derivatives and Surfactants at Solid Surfaces. An Ellipsometry Study

Abstract: The effect of surfactants on the adsorption properties of ethyl(hydroxyethyl)cellulose (EHEC) and its hydrophobically modified analogue (HM-EHEC) at the solid−liquid interface has been studied by ellipsometry. The adsorption characteristics of EHEC and HM-EHEC without the presence of surfactants are also presented. The polar silica surface and a hydrophobized silica surface were used as substrates. On the polar silica surface, a small addition of the anionic surfactant sodium dodecyl sulfate (SDS) caused a 3- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 47 publications
5
40
0
Order By: Relevance
“…Several cellulose ethers share the same behaviour and find use in many applications due to their adsorption properties and due to the fact that their temperature response can be modified by small changes in the degree of substitution. Examples include ethyl(hydroxyethyl)cellulose (EHEC), [5][6][7][8][9][10][11][12][13][14] methylcellulose (MC) [15][16] and hydroxypropylmethylcellulose (HPMC). 17 MC has been used to enhance drug release from microcrystals, 15 and functionalized by laminin it has been utilized in neural tissue engineering.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several cellulose ethers share the same behaviour and find use in many applications due to their adsorption properties and due to the fact that their temperature response can be modified by small changes in the degree of substitution. Examples include ethyl(hydroxyethyl)cellulose (EHEC), [5][6][7][8][9][10][11][12][13][14] methylcellulose (MC) [15][16] and hydroxypropylmethylcellulose (HPMC). 17 MC has been used to enhance drug release from microcrystals, 15 and functionalized by laminin it has been utilized in neural tissue engineering.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23] The inhibition of intermolecular association, due to hydroxypropyl groups, has also been indicated by NMR data. 21 The effect of temperature on adsorption and layer structure has been investigated for some thermo-responsive polymers, including poly(N-isopropylacrylamide) and EHEC, using techniques such as quartz crystal microbalance measurements, 2,27-30 ellipsometry 9,3 and surface force techniques. 8,[11][12]14 In earlier studies, the conformation of EHEC on hydrophobized mica was shown to be relatively flat, and the main driving force for the adsorption was suggested to be hydrophobic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Methodological developments by Bengt Jönsson, Mikael Landgren and Tommy Nylander laid the ground for the Ph D theses of Martin Malmsten (see, for example, references [ 148 , 149 ]) and Fredrik Tiberg (see below), focussing on polymer and surfactant adsorption, respectively. Much of the later work concerned mixed polymer–surfactant systems, with a thesis by Fredrik Joabsson (for example, see reference [ 150 ]) on mixed systems of non-ionic cellulose derivatives and ionic surfactants and much work by Tommy Nylander and students and coworkers on polyelectrolyte-surfactant systems (Yulia Samoshina, Eiji Terada, Marité Cárdenas etc.).…”
Section: Interfacial and Adsorption Aspects Of Polymers And Surfactanmentioning
confidence: 99%
“…Because of the high viscosity and shear thinning properties of solutions of this polymer, these formulations are easy to stir and does not drip [1]. EHEC has been used for research purposes extensively the last 15 years, and its surface characteristics have been studied rigorously [2][3][4][5][6][7][8][9][10]. By chemically cross-linking EHEC large changes in physically properties are obtained [11,12].…”
Section: Introductionmentioning
confidence: 99%